The Antioxidant Role of Soy and Soy Foods in Human Health - Gianluca Rizzo (MDPI AG, 2020)
Oxidative stress seems to play a role in many chronic diseases, such as cardiovascular diseases, diabetes, and some cancers. Research is always looking for effective approaches in the prevention and treatment of these pathologies with safe strategies. Given the central role of nutrition, the identification of beneficial healthy foods can be the best key to having a safe and at the same time effective approach. Soy has always aroused great scientific interest but often this attention is galvanized by the interaction with estrogen receptors and related consequences on health. However, soy, soy foods, and soy bioactive substances seem to have antioxidant properties, suggesting their role in quenching reactive oxygen species, although it was frequently mentioned but not studied in depth. The purpose of this review is to summarize the scientific evidence of the antioxidant properties of soy by identifying the human clinical trials available in the literature. A total of 58 manuscripts were individuated through the literature search for the final synthesis. Soy bioactive substances involved in redox processes appear to be multiple and their use seems promising. Other larger clinical trials with adequate standardization and adequate choice of biomarkers will fill the gap currently existing on the suggestive role of soy in antioxidant mechanisms.